(untitled) (Indian Journal of Child Health, 2020)
Background: Carotid intimal-medial thickness (CIMT) has recently emerged as one of the early markers of atherosclerosis and is helpful in providing direct evidence in comparison to traditional biochemical screening parameters. Objective: The objective of the study was to determine the change in the CIMT in children with celiac disease (CD) aged 1–14 years after 6 months of gluten-free diet (GFD). Materials and Methods: A total of 31 consecutive children with newly diagnosed CD (anti-tissue transglutaminase antibody titer of >10 U/L and intestinal biopsy histology of either Marsh Grade 3B or 3C) were enrolled in the study. CIMT was measured at the time of diagnosis and after 6 months follow-up on GFD by a single experienced radiologist who was blinded to the participant’s casestatus and risk factors. Results: The mean age of enrolled cases in our study was 7.58±3.38 years. The mean CIMT among enrolled children before GFD (0.0523±0.0069 cm) and after 6 months of GFD (0.0537±0.0063 cm) was greater than that of expected CIMT for this age (0.0411±0.5 cm). After 6 months of GFD, mean values on the right side (anterior wall, posterior wall, and mean; p=0.27, 0.794, and 0.557, respectively) or the left side (anterior wall, posterior wall, and mean; p=0.122, 0.063, and 0.078, respectively) were not statistically significantly. Conclusion: CIMT among children with CD was increased at enrolment but did not decrease significantly after 6 months of GFD. Further, studies are needed to be conducted with longer duration of follow-up for more insight into the subject.